2013
DOI: 10.1007/s12040-013-0271-5
|View full text |Cite
|
Sign up to set email alerts
|

Provenance and temporal variability of ice rafted debris in the Indian sector of the Southern Ocean during the last 22,000 years

Abstract: Ice rafted debris (IRD) records were studied in two sediment cores (SK200/22a and SK200/27) from the sub-Antarctic and Polar frontal regime of the Indian sector of Southern Ocean for their distribution and provenance during the last 22,000 years. The IRD fraction consists of quartz and lithic grains, with the lithic grains dominated by volcaniclastic materials. IRD content was high at marine isotope stage 2 but decreased dramatically to near absence at the Termination 1 and the Holocene. The concentration of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The paleo winter sea ice estimates for cores (a) SO136‐111 and (b) E27‐23 (solid blue lines) are plotted against the sea‐surface temperature record from (c) De Deckker et al []. The Scotia Sea sediment flux reported by Weber et al [] is shown in Figure d and the Indian Ocean IRD record of Manoj et al [] is shown in Figure e (brown lines). The TALDICE δ 18 O record from Stenni et al [] is shown in Figure f (purple line).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paleo winter sea ice estimates for cores (a) SO136‐111 and (b) E27‐23 (solid blue lines) are plotted against the sea‐surface temperature record from (c) De Deckker et al []. The Scotia Sea sediment flux reported by Weber et al [] is shown in Figure d and the Indian Ocean IRD record of Manoj et al [] is shown in Figure e (brown lines). The TALDICE δ 18 O record from Stenni et al [] is shown in Figure f (purple line).…”
Section: Discussionmentioning
confidence: 99%
“…Locations for the TALDICE and EPICA Dome C ice cores and marine sediment cores SO136-111, E27-23 (from the southwest Pacific), TN057-13PC4, PS2090/1094, and PS1654/1093 (from the Atlantic) are also indicated. (Cores SK200/27 [Manoj et al, 2013] and MD07-3134 [Weber et al, 2014], used to examine IBRD records, are identified.) Paleoceanography 10.1002/2014PA002764 FERRY ET AL.…”
Section: Analysis Of the Sea Ice Data Time Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ice core proxy based reconstruction revealed significant changes in Southern Hemispheric climate during the past several hundreds of years (Naik et al, 2010 a, b;Thamban et al, 2011 a,b;Thamban et al, 2013). The study revealed utility of shallow ice cores in reconstructing the past changes in major climatic modes like the El Niño Southern Oscillation (ENSO) and Southern Annular mode (SAM) (Naik et al, 2010 a).…”
Section: Ice Core Records Of Late Holocene Climate Variabilitymentioning
confidence: 94%
“…The early results suggested that shallow ice cores are indeed useful for regional climate reconstruction through a careful selection of core sites and a focussed study of proxy parameters (Nijampurkar et al, 2002;Thamban et al, 2006;Laluraj et al, 2009). The annually dated highresolution (annual) ice core studies revealed the utility of ice records to reconstruct the natural environmental processes as well as the polar and extra-tropical climatic teleconnections during the past hundreds of years (Naik et al, 2010 a,b;Thamban et al, 2011 a,b;Thamban et al, 2013;Antony et al, 2012;Laluraj et al, 2011;Laluraj et al, 2014;PAGES 2k Consortium, 2013;Rahaman et al, 2016). The increased focus on the well-dated ice cores from high accumulation regions of coastal Antarctica have improved our understanding on the recent climate variability in Antarctica and forcing mechanisms.…”
Section: Ice Core Records Of Late Holocene Climate Variabilitymentioning
confidence: 99%